2-Hydroxyglutarate Detection by Short Echo Time Magnetic Resonance Spectroscopy in Routine Imaging Study of Brain Glioma at 3.0 T. Issue 3 (May 2018) - Crisi, Girolamo; Filice, Silvano; Michiara, Maria; Crafa, Pellegrino; Lana, Silvia
Abstract : Objective: The objective of this study was to assess the effective performance of short echo time magnetic resonance spectroscopy (short TE MRS) for 2HG detection as biomarker of isocitrate dehydrogenase (IDH) status in all grade glioma (GL). Methods: A total of 82 GL patients were prospectively investigated by short TE MRS at 3.0 T as part of a multimodal magnetic resonance imaging study protocol. Spectral analysis was performed using linear combination model. Tumor specimens were diagnosed as IDH mutant or wild type according to the 2016 World Health Organization (WHO) classification of brain tumors. Spectra were analyzed for the presence of 2HG. The performance of short TE MRS was evaluated in terms of sensitivity, specificity, and positive and negative likelihood ratio on the overall sample and on GL WHO grades II and III and glioblastoma separately. Results: The specificity and sensitivity estimated on the overall sample were 88% and 77%, respectively. In GL WHO grades II and III, 100% specificity and 75% sensitivity were estimated. Conclusions: We reiterate the feasibility to identify IDH status of brain GL using short TE MRS at 3.0 T. The method can correctly detect 2HG as expression of IDH mutation in WHO grades II and III GL with a 100% specificity but a 75% sensitivity. In the evaluation of glioblastoma, short TE MRS performs poorly having a 17% false positive rate.